SPOPB: Reducing solid state drive write traffic for flash‐based key‐value caching. (21st November 2021) - Li, Zongwei; Feng, Dan; Hu, Yuchong; Lu, Mengting
Abstract: Flash‐based key‐value (KV) caching has received increasing attention in recent years with the advantages of flash‐based solid state drives (SSDs) in capacity and cost. By caching most data in SSD, the caching system can eliminate lots of time‐consuming requests to back‐end data stores to provide low‐latency services. To adapt to the unique technical constraints of flash memory, flash‐based KV caching adopts a slab‐based log‐structured management scheme in which the slab is the basic storage unit, and uses a small memory space as a write buffer to eliminate small random writes to SSD for consistent performance and increased lifetime of SSD. However, we have observed that under update‐intensive workloads with strong temporal locality, the slab‐based management in flash‐based KV caching introduces substantial SSD write traffic because of indistinguishable SSD flushing of hot items in slabs, which shortens the SSD lifetime and degrades the performance with increased erase operations. In this article, we first analyze the SSD write traffic in the flash‐based KV caching, and then propose a novel slab popularity‐based storage management scheme‐SPOPB, to extend SSD lifetime and improve performance. Our scheme identifies hot items using a self‐adaptive threshold to reorganize and classify slabs with both the hotness and size of items. Then SPOPB filters and retains the popular slabs containing hot items in the write buffer with redesigned replacement policy to reduce the SSD write traffic. Our experiments show that our design can effectively reduce the SSD write traffic by 63.6%, the erase counts by 55.6%, and improve the performance by 42%.